The two subunits of the human asialoglycoprotein receptor have different fates when expressed alone in fibroblasts - Shia, Michael A. (1989)
Two related polypeptides, H1 and H2, comprise the human asialoglycoprotein receptor (ASGP-R). Stable lines of murine NIH 3T3 fibroblasts expressing H1 alone or H2 alone do not bind or internalize the ligand asialoorosomucoid (ASOR), which contains triantennary oligosaccharides. In contrast, cells expressing H1 and H2 together bind and degrade ASOR with properties indistinguishable from those of the ASPG-R in human hepatoma HepG2 cells. Whether or not H2 is coexpressed, H1 is synthesized as a 40-kDa precursor bearing high-mannose oligosaccharides, processed to its mature 46-kDa form, and transported to the cell surface. In cells expressing only H1, homodimers and -trimers of H1 are formed. In contrast, when expressed in 3T3 cells without H1, H2 is synthesized as its 43-kDa precursor, bearing high-mannose oligosaccharides, but is rapidly degraded. When H1 and H2 are coexpressed in the same cell, the H1 polypeptide “rescues” the H2 polypeptide; H2 is processed to its characteristic 50-kDa mature form and is transported to the surface. We conclude that the human ASGP-R is a multichain heterooligomer, probably a trimer of H1 molecules in noncovalent association with one, two, or three H2 molecules, and that the two polypeptides normally interact early in biosynthesis.